Content Analysis of Bioenergetics’ Conceptual Presentation in Senior High School Biology Textbooks - Alforque, Jonemel M.; Jovero, Marijul B.; Bodanio, Cenando; Ecle, Niño; Picardal, Jay P. (Universitas Negeri Semarang, 2024)
Factors that bring about a low mastery level of bioenergetics, a core concept in biology, include relatively poor teaching-learning experience and low-quality textbooks, among others. To determine which textbook and teaching components have affected the low learning mastery of the topics in bioenergetics, the researchers analyzed the textbooks’ quality of content, language, layout, and figures, and the teachers’ experience, contentment, and challenges while teaching the topic, and effects to the learners. Using a sequential explanatory mixed method research design, ten (10) textbooks, and seven (7) teacher participants were purposively selected following a set of criteria. Descriptive and principal component analyses revealed that the textbooks' quality depends on two components: (1) competent and coherent visuals and content, and (2) consistency of style in the varied forms of assessment. Narrative analysis and Quasi-Statistics analysis revealed that teachers are not contented with the textbooks as they are inadequate to teach the subject matter. The lack of good learning materials, coupled with low competence to introduce the topics, resulted in the low mastery level of the learners. The researchers propose that periodic textbook assessment, retooling of teachers’ skills, and deepening teachers’ understanding are necessary to improve learners’ performance in bioenergetics. Finally, this paper is instrumental in providing educators, resources and curriculum developers, and researchers a feasible and practical path to improve textbook quality and address pedagogical gaps.